Determinants of foreign aid under alternative institutional arrangements - Hannelore Weck-Hannemann; Friedrich Schneider (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1988)
This study focuses on the determinants of bilateral and multilateral aid given to developing countries. We try to model the allocation process of different types of foreign aid and derive testable hypotheses using the public choice framework. The decisive motives are identified by explicitly taking into account the (rational) behavior of the main decision makers (voters/taxpayers, interest groups, government, national bureaucracy, and the officials in international organisations) as well as the alternative institutional arrangements under which the allocation process takes place. The statistical analysis reveals that, at least to some extent, the determinants used account for the aid allocation of each bilateral aid by DAC countries, credits by the World Bank, and multilateral aid given by the U.N. agencies and other international organisations (except the World Bank). However, the comparative evaluation of the estimates concerning the determinants of the different types of foreign aid turns out to be less satisfactory. There is only limited evidence for our graded hypotheses. Nevertheless, the estimates confirm the incremental hypothesis that the bureaucrats' behavior has the strongest impact on 16 bilateral aid. Also, bilateral aid commitments are partly influenced by recipients' need and political and military aspects, which also account for the allocation of multilateral aid by U.N. agencies and other international organisations. On the other hand, World Bank credits are not allocated out' of humanitarian motives. Yet, performance excellence turns out not to be as important as is theoretically expected.
Keywords: 330